Source Credibility and the Information Quality Matter in Public Engagement on Social Networking Sites During the COVID-19 Crisis - Shah, Zakir; Wei, Lu (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, people use social networking sites (SNSs) to seek social support, ease the move towards social distance, and to communicate and engage with one another. However, there is growing evidence that trustworthiness and quality of information can affect individuals’ online engagement behaviors. This study proposes a theoretical model to test people’s online engagement during the COVID-19 pandemic applying elaboration likelihood model (ELM). Through a questionnaire survey of 630 SNSs users, the study examines whether and how source credibility and information quality affect people’s online engagement during the COVID-19 pandemic. The model was tested using structure equation modelling. The findings show that source credibility and information quality have significantly positive relationship with perceived benefit, while negative and significantly associated with perceived risk. Furthermore, perceived benefit is a stronger predictor of online public engagement than the perceived risk. In order to improve online public engagement as a crisis response strategy, careful source’ selection and careful generation of online crisis information should not be overlooked.